Prospects of Halide Perovskites for Solar-to-Hydrogen Production - Huilong Liu; Tulja Bhavani Korukonda; Shubhra Bansal (Nanomaterials)
Solar-driven hydrogen generation is one of the promising technologies developed to address the world’s growing energy demand in an sustainable way. While, for hydrogen generation (otherwise water splitting), photocatalytic, photoelectrochemical, and PV-integrated water splitting systems employing conventional semiconductor oxides materials and their electrodes have been under investigation for over a decade, lead (Pb)- halide perovskites (HPs) made their debut in 2016. Since then, the exceptional characteristics of these materials, such as their tunable optoelectronic properties, ease of processing, high absorption coefficients, and long diffusion lengths, have positioned them as a highly promising material for solar-driven water splitting. Like in solar photovoltaics, a solar-driven water splitting field is also dominated by Pb-HPs with ongoing efforts to improve material stability and hydrogen evolution/generation rate (HER). Despite this, with the unveiling potential of various Pb-free HP compositions in photovoltaics and optoelectronics researchers were inspired to explore the potential of these materials in water splitting. In this current review, we outlined the fundamentals of water splitting, provided a summary of Pb HPs in this field, and the associated issues are presented. Subsequently, Pb-free HP compositions and strategies employed for improving the photocatalytic and/or electrochemical activity of the material are discussed in detail. Finally, this review presents existing issues and the future potential of lead-free HPs, which show potential for enhancing productivity of solar-to-hydrogen conversion technologies.